Clinical Cases in Coronary Rotational Atherectomy Complex Cases and Complications (Clinical Cases in Interventional Cardiology,, 2018)
This book describes and reviews a multitude of different scenarios in coronary rotational atherectomy. This technique is an integral tool in the coronary interventionalist's armamentarium and is essential in complex coronary interventions. Its use has grown more widespread over the last few years with interventional cardiologists tackling previously 'untreatable' coronary lesions. This has made it ever more important that interventionalists and all involved in the management of patients undergoing this procedure should be given practical information on best practice. Clinical Cases in Coronary Rotational Atherectomy contains over 25 clinical scenarios that reveal the wide extent of patient types, cardiovascular pathology and potential outcomes that the interventionist can experience with it. The book will therefore be of great value to interventional cardiologists, general cardiologists and cardiac surgeons, and all involved in the management of patients undergoing this procedure.